Adsorption of Cr(vi) onto a magnetic CoFe2O4/MgAl-LDH composite and mechanism study1. Issue 61 (4th July 2015) - Deng, Lin; Shi, Zhou; Peng, Xiaoxu
<x xml:space="preserve">Abstract</x> Magnetic materials as adsorbents can provide effective removal and quickly separate pollutants in wastewater treatment.